Pengembangan Instrumen Soal Tes Mata Pelajaran PJOK Berbasis Higher Order Thinking Skills (HOTS) - Afianto, Arif; Fiah, Rifda El; Hidayah, Nurul; Erfayliana, Yudesta (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
This research was conducted based on some problems that occur, namely the fact that when carrying out the teaching and learning process, students were still oriented towards the low order thinking skill (LOTS) and were not oriented towards the higher order thinking skills (HOTS) yet. In that case, instruments or questions were used during the evaluation process. In other words, measuring high order thinking skill has not been implemented yet, especially in physic (PJOK) subjects, so that teachers only focus on physical exercises in the field during the teaching and learning process. Teachers have not used physic (PJOK) assessments using HOTS yet. The type of research was research and development or R&D. This research referred to the Borg and Gall model which limited to 7 stages from the 10 stages including potential problems, data collection, product design, product validation, product revision, product testing, and design revision. The instrument used in this research was an assessment scale to determine the feasibility of the product and a Likert scale to determine the response of teachers and students to the feasibility and attractiveness of the product. The data analysis carried out was collecting data from validation results done by assessment experts, language experts, material experts and media experts, teachers and elementary students. The result of analysis showed that questions and tests based on higher order thinking skills (HOTS) for class V physic subject (PJOK) was developed "Very decent or Very interesting" to be used as a measuring tool for students in training their high order thinking skills. These results were obtained based on validation from assessment experts, material experts, language experts and material experts. The assessment results from the assessment experts showed the "Very decent" category with a percentage value of 92.5%. The results of the material expert assessment reached the "Very decent" category with a percentage value obtained of 90%. Then, the results of the language expert’s assessment reached the "Very decent" category with the percentage value obtained reaching 92.25%.